Pemberian topical application flour untuk initial caries pada pasien anak - Shabrina, Fadhila Nurin; Hartomo, Bambang Tri (Poltekkes Kemenkes Yogyakarta, 2020)
Oral Health maintenances are very important to do to achieve optimal body health, so that recommended to start from the period of deciduous teeth. The health of deciduous teeth in children will be a determinant regarding the condition of permanent teeth that will replace them. The most common oral health problem is dental caries. Data from the 2018 Basic Health Outcomes Research shows the prevalence of caries in Indonesia is 57.6%. There are three kinds of prevention that can be done to prevent caries: primary, secondary, and tertiary prevention. The earliest action is primary prevention. Primary measures to prevent caries are effective for teeth that are still healthy or when the initial caries occurs. Initial caries characterized by demineralized tooth enamel but no cavities have been formed. Primary stage of caries prevention includes dental health education, maintaining dental health, regular dental examinations, administering fissure sealants, and administering topical application fluoride (TAF). TAF is one of the most effective in preventing caries. TAF is a simple technique to application fluoride solutions by dental practitioners and can be applied easily. This treatment is highly recommended for children who have recently erupted in the mouth to strengthen the enamel layer of the teeth.